"Larva", the language in polyglot pyrotechny of a Don Juan’s Babel night - Medina, Dante (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Larva, Babel de una noche de San Juan, is a great monument of European literatures, and one of the common European’s myth is the Don Juan Myth. Julián Ríos approaches it in this Babelic novel by making a polyglot combination of the languages of this continent, forcing all them to speak among themselves in an astonishing and dazzling verbal pyrotechnics, with a virtuous juggling of interminable and chained word games. He resorts to semiotics, semantics, phonetics, syntax, but also all cultural intertextualities, and the questioning of novel, fabulation, and the entire narratology. It is a summum of our literary history.